Implementasi Media Wordwall pada Pembelajaran Bahasa Indonesia dalam Meningkatan Hasil Belajar Siswa Di Sekolah - Putri, Marta Diniyah; Salamah, Salamah; Romadhianti, Rona (Linguistik : Jurnal Bahasa dan Sastra, 2025)
Technology has penetrated the education sector in Indonesia but its unoptimal utilisation has resulted in a decrease in student interest and learning outcomes in Indonesian language subjects. This study examines the use of Wordwall media in Indonesian language learning to improve learning outcomes on synonyms and antonyms. This research uses a qualitative method, which involves interviews, observations, tests, and student feedback. The formulation of the problem in this study is how the use of Wordwall media can improve student learning outcomes on the material of synonyms and antonyms and how students respond to the use of Wordwall media in Indonesian language learning in class V SDN 02 Sumberejo. Data analysis includes collection, reduction, interpretation, and conclusion. The results showed a significant increase of 93% above the average KKM of 75 and supported by feedback from fifth grade students of SDN 02 Sumberejo.